Analysis of Transmissible and Nontransmissible Components of Variation in Human Physique - Kaczmarek, Maria (Anthropological Review, 1996)
The paper is aimed at decomposition the continuously varying phenotype into components due to transmissible and nontransmissible factors. The linear causal model (path analysis) was applied to incorporate the contribution of environmental sources of variation (described in terms of indices of socioeconomic status) to familial resemblance on physique (height and weight) in 342 nuclear families. Parameters of the causal model were estimated according to the TAU transmission model of Rice, Cloninger, Reich [1978] and linear constraints placed upon the parameters were tested. The proportion of total phenotypic variance accounted for by genetic and environmental transmissible factors was estimated to be 62% for height and 38% for weight.